Spinach Methanolic Extract Attenuates the Retinal Degeneration in Diabetic Rats - Rocio Bautista-Pérez; Agustina Cano-Martínez; Elisa Gutiérrez-Velázquez; Martín Martínez-Rosas; Rosa M. Pérez-Gutiérrez; Francisco Jiménez-Gómez; Javier Flores-Estrada (MDPI AG, 2021)
It has been suggested that spinach methanolic extract (SME) inhibits the formation of advanced glycation end products (AGEs), which are increased during diabetes progression, so it is important to know if SME has beneficial effects in the diabetic retina. In this study, in vitro assays showed that SME inhibits glycation, carbonyl groups formation, and reduced-thiol groups depletion in bovine serum albumin incubated either reducing sugars or methylglyoxal. The SME effect in retinas of streptozotocin-induced diabetic rats (STZ) was also studied (n = 10) in the normoglycemic group, STZ, STZ rats treated with SME, and STZ rats treated with aminoguanidine (anti-AGEs reference group) during 12 weeks. The retina was sectioned and immunostained for Nε-carboxymethyl lysine (CML), receptor RAGE, NADPH-Nox4, inducible nitric oxide synthase (iNOS), 3-nitrotyrosine (NT), nuclear NF-κB, vascular endothelial growth factor (VEGF), glial fibrillary acidic protein (GFAP), S100B protein, and TUNEL assay. Lipid peroxidation was determined in the whole retina by malondialdehyde (MDA) levels. The results showed that in the diabetic retina, SME reduced the CML-RAGE co-localization, oxidative stress (NOX4, iNOS, NT, MDA), inflammation (NF-κB, VEGF, S100B, GFAP), and apoptosis (p < 0.05). Therefore, SME could attenuate the retinal degeneration by inhibition of CML-RAGE interaction.